Les mots et les choses : une archéologie des sciences humaines - Foucault, Michel 1926-1984 (Paris Gallimard, 1966)
Today's human sciences are more than just knowledge. Michel Foucault analyses their appearance, their reciprocal links and the philosophy that supports them. It is only recently that 'man' has made his appearance in our knowledge. It is a mistake to believe that he has been an object of curiosity for thousands of years: he was born of a mutation in our culture. Michel Foucault studied this mutation, from the 17th century onwards, in the three fields in which classical language - which was identified with Discourse - had the privilege of being able to represent the order of things: general grammar, analysis of wealth, natural history. At the beginning of the nineteenth century, a philology was formed, a biology as well, a political economy. Things obey the laws of their own becoming and no longer those of representation. The reign of Discourse came to an end and, in the place it left empty, 'man' appeared - a man who spoke, lived, worked, and thus became the object of possible knowledge.This is not a 'history' of the humanities, but an archaeology of what is contemporary. And a critical awareness: for the day, perhaps soon, when these conditions change again, 'man' will disappear, releasing the possibility of a new thought.
Keywords: Philosophy; Sociology